USM L’OREAL-UNESCO AWARD RECIPIENTS URGED TO BE GLOBAL PLAYERS IN RESEARCH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUALA LUMPUR, 6 October 2016 – Two Universiti Sains Malaysia (USM) scientists, Dr. Fatehah Mohd Omar and Dr. Nethia Mohana Kumaran were the proud recipients of the prestigious 2016 L’OrealUNESCO for Women in Science Awards in a ceremony held here today.